Clinical and magnetic resonance imaging feature differences between solitary and multiple type Langerhans cell histiocytosis involving the craniofacial bone. Issue 1 (January 2022) - Matsushita, Shu; Shimono, Taro; Okuma, Tomohisa; Inoue, Takeshi; Manabe, Takao; Miki, Yukio
Abstract: Purpose: To investigate the clinical and contrast-enhanced magnetic resonance imaging (MRI) features of craniofacial bone Langerhans cell histiocytosis (LCH) and discuss the differences between a solitary lesion group (SLG) and multiple lesions group (MLG). Method: This study included 22 consecutive patients with pathologically proven LCH who underwent contrast-enhanced MRI. The clinical data and MRI features were retrospectively assessed. Results: The mean patient age was 5 years, and 15 patients were male. The frontal bone was the most frequently affected bone. Ten and 12 patients were classified into the SLG and the MLG, respectively. The following MRI features were observed in >50% cases: T1WI hyperintensity in 15 (68%) cases, T2WI hyperintensity in 16 (73%) cases, bulging sign in 18 (82%) cases, concentric or eccentric soft tissue mass formation in 13 (59%) cases, soft tissue edema in 16 (73%) cases, any grade of bone marrow edema in 16 (73%) cases, surrounding bone enhancement in 17 (77%) cases, and surrounding soft tissue enhancement in 16 (73%) cases. Patient age was significantly higher in the SLG than that in the MLG ( P = 0.0014). Perilesional bone marrow edema and enhancement were significantly more prominent in the SLG than in the MLG ( P = 0.032, P = 0.040). Conclusions: Contrast-enhanced MRI showed additional significant findings of mainly the surrounding details. Older age, extensive bone marrow edema, and enhancement may indicate solitary-type LCH rather than multiple-type LCH. These differences may help distinguish between solitary- and multiple-type LCH, which have different treatment strategies. Graphical abstract: Image 1 Highlights: Patient age at presentation was higher in the SLG than that in the MLG. The SLG showed more extensive bone marrow edema and enhancement than the MLG. Clinical and MRI features may help differentiate LCH manifestation types. Abstract : Langerhans cell histiocytosis; Craniofacial bone; Magnetic resonance imaging.